Deoxydehydration of vicinal diols and polyols catalyzed by pyridinium perrhenate salts. Issue 23 (25th October 2017) - Morris, Danny S.; van Rees, Karlotta; Curcio, Massimiliano; Cokoja, Mirza; Kühn, Fritz E.; Duarte, Fernanda; Love, Jason B.
Abstract : Simple ammonium and pyridinium perrhenate salts were evaluated as catalysts for the deoxydehydration (DODH) of diols into alkenes. Abstract : Simple ammonium and pyridinium perrhenate salts were evaluated as catalysts for the deoxydehydration (DODH) of diols into alkenes. Pyridinium perrhenates were found to be effective catalysts at much lower temperatures than those in previous reports, outperforming primary, secondary, and tertiary ammonium salts, while quaternary ammonium salts are effectively inactive. The mechanism of reaction was studied computationally using DFT calculations which indicate that proton shuttling between the ion pair is intrinsic to the mechanism and that the reduction of rhenium by the phosphine occurs before the diol condensation.